A Smartphone Application for Teamwork and Communication in Trauma: Pilot Evaluation "in the Wild". (February 2022) - Catchpole, Ken; Privette, Alicia; Roberts, Laura; Alfred, Myrtede; Carter, Brittan; Woltz, Erick; Wilson, Dulaney; Crookes, Bruce
Objective: To evaluate the potential for a smartphone application to improve trauma care through shared and timely access to patient and contextual information. Background: Disruptions along the trauma pathway that arise from communication, coordination, and handoffs problems can delay progress through initial care, imaging diagnosis, and surgery to intensive care unit (ICU) disposition. Implementing carefully designed and evaluated information distribution and communication technologies may afford opportunities to improve clinical performance. Methods: This was a pilot evaluation "in the wild" using a before/after design, 3 month, and pre- post-intervention data collection. Use statistics, usability assessment, and direct observation of trauma care were used to evaluate the app. Ease of use and utility were assessed using the technology acceptance model (TAM) and system usability scale (SUS). Direct observation deployed measures of flow disruptions (defined as "deviations from the natural progression of an procedure"), teamwork scores (T-NOTECHS), and treatment times (total time in emergency department [ED]). Results: The app was used in 367 (87%) traumas during the trial period. Usability was generally acceptable, with higher scores found by operating room (OR), ICU, and neuro and orthopedic users. Despite positive trends, no significant effects on flow disruptions, teamwork scores, or treatment times were observed. Conclusions: Pilot trials of a clinician-centered smartphone app to improve teamwork and communication demonstrate potential value for the safety and efficiency of trauma care delivery as well as benefits and challenges of "in-the-wild" evaluation.